Short communication. Screening of sorghum genotypes for resistance to damage caused by the stem borer Chilo partellus (Swinhoe) - Marulasisdesha, K.N.=700 1 Sankar, M.; Rama Gouda, G.K.
(Es, En)
ilus., 9 ref.
Keywords: SORGHUM BICOLOR; INSECTOS DAÑINOS DEL TALLO; RESISTENCIA A AGENTES DAÑINOS; CHILO PARTELLUS; LEPIDOPTERA; INSECTA; ESPAÑA